Implementation of Curator's Authority to Filing Actio Pauliana Suit (Study of Case Verdict Number 01/Pdt.Sus/ActioPauliana/2016/PN.Niaga.Jkt.Pst) - Anindra, Charla Ferina (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
To protecting the interest of creditors which are prejudiced due to legal actions conducted by debtors, Law Number 37 Year 2004 provides a legal action through actio pauliana. The research based on Verdict Number 01/Pdt.Sus/ ActioPauliana/2016/PN.Niaga.Jkt. The authority of Tommy Simorangkir as a curator in filing an actio pauliana suit towards the debtor’s bankrupt assets in the form of a plot of land which is owned by the bankrupt and 2 (two) other persons, and whether the legal consideration of the panel of judges in deciding the case has been correct or incorrect. The type of research which the author uses in this research is a normatif research and uses the statue and case approach. The data which is used in this research are secondary data by using legal materials. The result finds that the authority to file an actio pauliana suit in a bankruptcy case is possessed by curators and Tommy Simorangkir has the authority to file actio pauliana although the asset is not only owned by the debtor alone, however, actio pauliana filed in the said case shall be rejected since it is not proven that the debtor is aware that their conduct is prejudicial to the creditor.